Interaksi Trofik Jenis Serangga di atas Permukaan Tanah dan Permukaan Tanah Beberapa Pertanaman Varietas Jagung (Zea mays Linn.) - Gery Lineker Purba; Marheini Marheini; Syahrial Oemry (Jurnal Agroekoteknologi, 2015)
The aim of the reasearch was to know the tropic interaction of insect on the soil surface and above of soil surface for many varieties of corn (Zea mays Linn.) and index diversity value of insect of corn. The research was conducted in BBI of Tanjung Slamat and Agriculture Pest Laboratory in University of Sumatera Utara, Medan from November (2013) until March (2014). The insect trapped used yellow stiky trap and pitt fall trap. The result of the research showed that insects caught each consist of 9 ordo and 33 family. The highest relative density values in PRG NK603 (application of glyphosate) variety was 16.691% and the lowest was 0.681%. The highest relative density values in PRG NK603 variety was 16.363% and the lowest was 0.578%. The highest relative density values in C7 variety was 15.499 % and the lowest was 0.577 %. The highest relative density values in DK979 variety was 15.073 % and the lowest was 0.450 %. Shanon-Weiner (H’) Index diversity value of insect in PRG NK603 (application of glyphosate) variety was 2.950309 (standart), in PRG NK603 was 3.006432 (stable), in C7 variety was 3.051692 (stable), and in DK979 variety was 3.082916 (stable).Keywords : interaction, insects, corn, trap